2019
DOI: 10.1111/papt.12208
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from insecure attachment dimensions to paranoia: The mediating role of hyperactivating emotion regulation versus blaming others

Abstract: Objectives There is evidence of associations between insecure attachment and paranoia, but we do not yet fully understand the mediating mechanisms. Attachment theory emphasizes differential relatedness of insecure attachment dimensions (i.e., anxiety vs. avoidance) with specific emotion regulation styles (ER). We tested whether the associations between attachment anxiety versus avoidance and paranoia were mediated specifically by hyperactivating (i.e., the use of emotion‐amplifying strategies: self‐blame, rumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 63 publications
4
34
0
1
Order By: Relevance
“…Based on existing attachment theories and targeting athletes, this study was conducted to investigate the effects of coach–athlete attachment on the SWB of athletes, as well as their underlying mechanisms, and some constructive results were acquired. First, it was found that attachment anxiety and attachment avoidance toward coaches were negatively correlated with the SWB of athletes, which is an interesting result that is consistent with the conclusions of other researchers [ 4 , 12 , 13 , 14 ]. In the Chinese cultural context, the coach–athlete relationship is an important source of attachment for athletes and has an inevitable effect on the SWB of athletes; as the proverb goes, “one day as a teacher, a life as a father.” Unlike for the typical coach–athlete relationship [ 28 ] in which the athlete spends time at their own home and sees the coach for a smaller portion of the day (save for when the team travels), Chinese athletes considered in the current study live together with their coaches all day, and the coach–athlete relationship can also moderately affect the life satisfaction and emotional experience of athletes [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Based on existing attachment theories and targeting athletes, this study was conducted to investigate the effects of coach–athlete attachment on the SWB of athletes, as well as their underlying mechanisms, and some constructive results were acquired. First, it was found that attachment anxiety and attachment avoidance toward coaches were negatively correlated with the SWB of athletes, which is an interesting result that is consistent with the conclusions of other researchers [ 4 , 12 , 13 , 14 ]. In the Chinese cultural context, the coach–athlete relationship is an important source of attachment for athletes and has an inevitable effect on the SWB of athletes; as the proverb goes, “one day as a teacher, a life as a father.” Unlike for the typical coach–athlete relationship [ 28 ] in which the athlete spends time at their own home and sees the coach for a smaller portion of the day (save for when the team travels), Chinese athletes considered in the current study live together with their coaches all day, and the coach–athlete relationship can also moderately affect the life satisfaction and emotional experience of athletes [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…The two dimensions can be categorized into high and low levels; the attachment style, including low attachment anxiety and low attachment avoidance, is called secure attachment, while all other combinations are considered insecure attachment [ 13 , 14 ]. As has been previously reported, attachment is closely related to SWB [ 4 , 12 , 13 , 14 ]. For instance, Guardia found secure attachment to be positively correlated with SWB [ 15 ].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…All participants were paid for participating in the study. Data related to the social exclusion paradigm (Lincoln et al 2018;Sundag et al 2018) and questionnaire data (Ascone et al, 2020) have been published elsewhere. Here, we analyze the data from the questionnaires and from the experimental paradigm on emotion-regulation.…”
Section: Methodsmentioning
confidence: 99%
“…Problems in identifying and describing one´s emotions were assessed with the German version of the Toronto Alexithymia Scale (TAS-20;Bach et al 1996). It consists of 20 items that are rated on a 5-point scale ranging from 1 (not applicable) to 5 (always applicable).…”
Section: Alexithymiamentioning
confidence: 99%